How Stella got her groove back - McMillan, Terry (New York : Viking Press, 1996)
A holiday in Jamaica turns into sizzling romance for 42-year-old Stella Payne, a black divorcee and financial security analyst, when she meets Winston Shakespeare, a local assistant cook. Stella invites him to San Francisco to show him off to friends and to her 11-year-old son, and Shakespeare is a hit. Only problem, Shakespeare is 20 years old.
Keywords: DIVORCED WOMEN